Statewide pedestrian and bicycle planning handbook. - Biton, Anna; Daddio, David; Andrew, James (My University, 2014)
This handbook is designed to help State departments of transportation (DOTs) develop or update State pedestrian bicycles plans. Based on research including interviews with nine State DOTs and critical evaluation of documents from 15 States, this handbook covers statewide planning from plan inception and scoping to engaging stakeholders and the general public; developing goals, objectives and strategies; collecting and analyzing data; linking to the larger statewide transportation planning process; and implementation. For each stage of the planning process, this handbook uses recent experiences and noteworthy practices from DOTs around the country, helping inform a new generation of statewide nonmotorized planning and implementation.
Keywords: Individualverkehr; Fahrradverkehr; Fußgängerverkehr; Verkehrssicherheit; Verkehrsplanung; Radverkehrsplanung; Bürgerbeteiligung; Radverkehrssicherheit